Mechanical properties of Carbon-matrix composites for a blade runner's artificial leg. Issue 1 (1st January 2021) - Ismail, Rifky; Paras Utami, Dewi; Arid Irfai, Mochamad; Jamari, J.; Bayuseno, A.P.
Abstract: The use of fiber-reinforced polymer (FRP) for prosthetic devices is now very common. Various polymer resins have been reinforced the fiber yielding composite with better strength-to-weight characteristics compared to a single material and also providing better biocompatibility. The purpose of the present study was to examine a single glass, carbon fiber with various matrix combinations for a composite of a blade runner's artificial leg. The polymer matrices, namely epoxy bakelite (ER), casting (CR), orthocryl (OR), and polyester (PR) resins were selected, while evaluations of mechanical and physical properties of composite samples including tensile and bending, impact, hardness, and density were performed. Results showed that the combination of the fiber-orthocryl resin provided the best composite with the highest average tensile strength (483.94 MPa). Similarly, the highest average bending stress could be manufactured by combining fiber and orthocryl resin (494.17 MPa), but having the lowest average value of impact energy (5.6 J). The highest average hardness value could be provided by carbon—polyester (PR) combination (21.10 VHN), while the high specific strength of the composite could be achieved by the OR composite. The combination of carbon fiber and epoxy matrices is potential for use for a blade runner's artificial leg because of having a better energy absorption on impact load. The outcome of the study may also assist as a reference for future work in the area of prosthetic material.